US-CHINA RELATIONS: TRADE WAR AND THE QUEST FOR GLOBAL HEGEMONY (Journal of International Studies, 2021)
This article attempts to provide an alternative perspective on the US-China trade war by integrating power transition theory and the concept of soft power in examining the nature of the trade war and conditions that fuelled it. The discussion also includes the possibility of the emergence of a new global order led by China beyond the trade war. This study used a qualitative approach by analysing primary and secondary sources such as speeches of representatives from both China and the US, books, journal articles, newspaper articles and research by both national and international organisations. The findings revealed that the main trigger of the trade war was not trade deficits or unfair practices, as other literature has suggested, but rather a desire by the US to prevent the decline of American hegemony. We argue that there are three reasons why China cannot form a new global order and replace the US as a global hegemon within the next decade. First, following the trade war, there is growing wariness about Chinese firms and investments, globally. Second, China’s soft power is relatively ineffective, and its culture less appealing to Third World countries as compared to the US’s. Finally, unlike the US, China does not have a strong and expansive network of allies supporting its quest for global leadership.